Effects of electron beam irradiation on cork volatile compounds by gas chromatography mass spectrometry - Careri, M.; Mazzoleni, V.; Musci, M.; Molteni, R. (CHROMATOGRAPHIA, 1999)
The effects of electron beam irradiation on cork volatile compounds was studied at different doses (25, 100, 1000 kGy), Volatiles we:re isolated from cork using the dynamic headspace-sampling technique, then identified by gas chromatography-mass spectrometry (GC-MS). Similar gas chromatographic profiles were obtained for non-irradiated and irradiated corks. Quantitative differences induced by the three doses were evaluated by calculating peak areas for each compound identified. The quantitative differences between non-irradiated corks and those irradiated at 25 kGy were significant for only a few substances, when:as significant quantitative differences were found in samples irradiated at 100 and 1000 kGy. For these doses, the content of volatile compounds generally increased, especially that of aliphatic hydrocarbons and carbonyl compounds. The behaviour of radiolytic hydrocarbons indicates that the mechanisms proposed for their formation in irradiated foods could take place even in cork.
The following values have no corresponding Zotero field: pub-location: ABRAHAM-LINCOLN-STRABE 46, POSTFACH 15 47, D-65005 WIESBADEN, GERMANY publisher: VIEWEG
Keywords: cork volatiles; dynamic headspace sampling; electron beam irradiation; gas chromatography mass spectrometry; radiolysis-induced compounds

Effects of electron beam irradiation on cork volatile compounds by gas chromatography mass spectrometry - Careri, M; Mazzoleni, V; Musci, M; Molteni, R (CHROMATOGRAPHIA, 1999)
The effects of electron beam irradiation on cork volatile compounds was studied at different doses (25, 100, 1000 kGy), Volatiles we:re isolated from cork using the dynamic headspace-sampling technique, then identified by gas chromatography-mass spectrometry (GC-MS). Similar gas chromatographic profiles were obtained for non-irradiated and irradiated corks. Quantitative differences induced by the three doses were evaluated by calculating peak areas for each compound identified. The quantitative differences between non-irradiated corks and those irradiated at 25 kGy were significant for only a few substances, when:as significant quantitative differences were found in samples irradiated at 100 and 1000 kGy. For these doses, the content of volatile compounds generally increased, especially that of aliphatic hydrocarbons and carbonyl compounds. The behaviour of radiolytic hydrocarbons indicates that the mechanisms proposed for their formation in irradiated foods could take place even in cork.
Keywords: cork volatiles; dynamic headspace sampling; electron beam irradiation; gas chromatography mass spectrometry; radiolysis-induced compounds